Acute radiotherapy-associated oral pain may promote tumor growth at distant sites - Meneses, Constanza S.; Gidcumb, Emily M.; Marcus, Karen L.; Gonzalez, Yarines; Lai, Yen Hao; Mishra, Santosh K.; Lascelles, B. Duncan X.; Nolan, Michael W. (Frontiers in Oncology, 2023)
Patients developing acute radiotherapy induced dermatitis or oral mucositis commonly experience pain. When severe, thisradiotherapy-associated pain (RAP) can necessitate treatment breaks; unfortunately, in a variety of cancers, prolongation of the radiotherapy course has been associated with early cancer relapse and/or death. This is often attributed to accelerated repopulation, but it is unknown whether pain or pain signaling constituents might alter tumor behavior and hasten metastatic disease progression. We studied this by testing the hypothesis that severe acute RAP at one site can hasten tumor growth at a distant site. Mice underwent single fraction tongue irradiation (27 Gy, or 0 Gy “sham” control) to induce severe glossitis. At the time of maximal oral RAP, one of three luciferase-transfected tumor cell lines were injected via tail vein (4T1, B16F10, MOC2; each paired to their syngeneic host: BALB/c or C57BL/6); tumor burden was assessed via in vivo transthoracic bioluminescence imaging and ex vivo pulmonary nodule quantification. Survival was compared using Kaplan-Meier statistics. Tongue irradiation and resultant RAP promoted lung tumor growth of 4T1-Luc2 cells in BALB/c mice. This effect was not a result of off-target radiation, nor an artefact of environmental stress caused by standard (subthermoneutral) housing temperatures. RAP did not affect the growth of B16F10-Luc2 cells, however, C57BL/6 mice undergoing tail vein injection of MOC2-Luc2 cells at the time of maximal RAP experienced early lung tumor-attributable death. Lung tumor growth was normalized when RAP was reduced by treatment with resiniferatoxin (300 µg/kg, subcutaneously, once). This research points towards radiation-induced activation of capsaicin-responsive (TRPV1) neurons as the cause for accelerated growth of tumors at distant (unirradiated) sites.